2013
DOI: 10.1177/0263276413488963
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Techniques: Or the End of the Intellectual Postwar Era in German Media Theory

Abstract: This paper seeks to introduce cultural techniques to an Anglophone readership. Specifically geared towards an Anglophone readership, the paper relates the re-emergence of cultural techniques (a concept first employed in the 19th century in an agricultural context) to the changing intellectual constellation of postwar Germany. More specifically, it traces how the concept evolved from – and reacted against – so-called German media theory, a decidedly anti-hermeneutic and anti-humanist current of thought frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 13 publications
0
27
0
10
Order By: Relevance
“…The speaker suggested the notion of cultural techniques (Siegert 2013, Winthrop-Young 2013 for bringing together discussions on materiality, practices as well as signs and text into the historical analysis of software. Using the example of business games, he suggested that practices often preclude discourse.…”
Section: Book Reviewsmentioning
confidence: 99%
“…The speaker suggested the notion of cultural techniques (Siegert 2013, Winthrop-Young 2013 for bringing together discussions on materiality, practices as well as signs and text into the historical analysis of software. Using the example of business games, he suggested that practices often preclude discourse.…”
Section: Book Reviewsmentioning
confidence: 99%
“…Esta dupla-hélice é bastante evidente no desenvolvimento mais recente da tradição alemã, o conceito de Kulturtechnik (Siegert, 2012(Siegert, , 2013Geoghegan, 2013), que pode ser traduzido como técnicas culturais, mas cujas raízes agrícolas traduziriam talvez melhor por "téc-nicas de cultivo". Entendidas enquanto tais, a racionalização e a sistematização da lavoura acarreta uma matriz de práticas que estabelece uma lógica dentro do solo, territorializando-o, e codifica as relações entre homens e máqui-nas para o seu cultivo.…”
Section: Medium/formaunclassified
“…O resultado são distinções culturais, tanto dentro da terra territorializada quanto entre terras diferentes (Geoghegan, 2013). No entanto, assim que tem início o processo de "aculturação", inicia-se também o de "desculturação", que desestabiliza os códigos culturais, apaga signos, desprograma a codificação e, no limite, desterritorializa o território, fazendo-o passar por novos processos cultivantes (Siegert, 2013).…”
Section: Medium/formaunclassified
See 2 more Smart Citations